The Chicago monetary growth-rate rule: Friedman on Simons reconsidered - TAVLAS, G.S.; ASCHHEIM, J. (PSL Quarterly Review, 2013)
The work takes up a series of issues pertaining to the monetary interpretation of Friedman and Simons. The authors find that espousal of a monetary rule involves, foremost, confidence in the extrapolability of long-term statistical trends, particularly with respect to velocity. The initial formulation of the monetary hypothesis of the Great Depression is linked to an entirely overlooked original contribution by William Foster and Waddill Catchings. Their contribution these authors essentially anticipates views set forth by Friedman and Simons, and already included the formulation of the monetary growth-rate rule. JEL: B31